Analisisi Efisiensi Penggunaan Data Berbasis Digitalisasi Dan Keamanan Arsip pada PT Angkasa Pura II Jakarta Periode 2019 – 2020 (24 Bulan) (Studi Kasus Dimasa Pandemi Covid-19) - Sri Retnaning Sampurnaningsih; Agus Suharyadi; Nani Rusnaeni; Juni Sukasmono; Retno Wulansari (Universitas Pamulang, 2021)
Technological advances in the 4.0 era have made digitalization technology develop more rapidly where information can be obtained more quickly and this of course has an impact on the efficiency of data use in the company. This study aims to analyze the efficiency of data use based on data digitization and archive security at PT Angkasa Pura II, during the Covid-19 pandemic. The method used in this study is causal associative with multiple linear regression analysis, classical assumption test and hypothesis testing. The sample in this study uses digitized data, data security and frequency of data usage. The results of this study are data digitization (X1) shows a significant effect on the efficiency of data use (Y). Archive security (X2) shows a significant effect on the efficiency of data use (Y). Furthermore, data digitization and archive security simultaneously have a significant effect on the efficiency of data use. Statistically, the coefficient of determination with an R-square value of 0.489 indicates that the contribution of data digitization and archive security to the efficiency of data use is 48.9% and the remaining 51.1% can be explained from other variables. It can be concluded that with the development of digitalization technology, it is easier for people to use data. The development of digitalization technology, both directly and indirectly, has affected the company's performance which is becoming more efficient in the use of its data so that it has an impact on faster information obtained that can support the decision-making process in a company.Keywords: Digitization, Archive Security, Data Use Efficiency